Envisioning Sociology Victor Branford, Patrick Geddes, and the Quest for Social Reconstruction - Scott, John (State University of New York Press, 2013)
Envisioning Sociology is a landmark work, the first major study of the founding of sociology in Britain and the enormous contributions made by the intellectual circle led by Victor Branford and Patrick Geddes. Authors John Scott and Ray Bromley chronicle the biographical connections and personal partnerships of the circle's key participants, their international connections, their organization-building work, and the business activities that underpinned their efforts. Branford and Geddes fashioned an ambitious and wide-ranging interdisciplinary vision, drawing on geography, anthropology, economics, and urban planning, in addition to sociology. This vision was an integral part of a project of social reconstruction, a "third way" eschewing both liberalism and communism in favor of cooperation, redistribution, and federalism. Envisioning Sociology uncovers a previously hidden history of the social sciences, giving readers a fascinating glimpse into early twentieth-century social science and political economy, while demonstrating the contemporary relevance of the ideas of these underrated figures. Although Branford and Geddes failed to establish the grand sociology they envisioned, their ideas helped develop the theory and practice of community development, participatory democracy, bioregionalism, historic preservation, and neighborhood upgrading.